Studying оf musical culture as the important candition of development of professional tninking al the future teachers of music - Shahlievich, O.A. (Pedagogy of Higher and Secondary Education, 2006)
The article of the gnen research consists of theoretical ground of choice and use of different achievements of world and national cultures, directed on creative development of professional thought of future music masters.